Application of Auriculotherapy for Post-Burn Scar Syndrome in Young Adults with Major Burns - Cha-Chun Chen; San-Pei Chen; Shu-Yu Lyu; Chung-Hua Hsu (Medical Association of Pharmacopuncture Institute, 2021)
Background : A burn scar is a type of hypertrophic scar that can cause significant clinical symptoms, discomfort, and post-burn scar (PBS) syndrome in up to 77% of patients with burn injuries. Medication and rehabilitation are rarely effective at managing patient discomfort, and both laser and surgical interventions are postponed until the scar stabilizes and discomfort is tolerable. Objectives: The present study was conducted to investigate the effectiveness of auricular acupuncture among burn victims from the Formosa Color Dust Explosion in Taiwan. Methods : We enrolled 31 victims of the 2016 Formosa Color Dust Explosion who met the study inclusion criteria. The intervention involved placement of magnetic beads over the auricular Shenmen and Subcortex acupoints on one ear. Patients performed selfmassage five times per day, and both magnet beads were removed between the fifth and seventh days during the sessions. Several evaluation tools were used to assess clinical symptoms: the visual analogue scale for pain assessment, Burn Man Itch Scale for perceived patient itchiness, 5-D Pruritus Scale for sleep quality, and heart rate variability (HRV) for effects on the autonomic nervous system. Results : The clinical symptoms were significantly decreased following the intervention, but the effect did not endure. The normal-to-normal heart rate interval, heart rate analysis abnormalities, and very low frequency heart rate were significantly decreased among patients with abnormal HRV (SD < 40) following treatment. Conclusion : Stimulation of the auricular Shenmen and Subcortex acupoints may effectively reduce pain, itchiness, and sleep disturbances among patients with PBS syndrome.